Penerapan Metode Promethee II Dalam Sistem Pendukung Keputusan Pemilihan Penerima Bantuan Bedah Rumah Di Desa Hutapaung - Farlin Marupa Pasaribu (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
House renovation is one of the government assistance programs that aims to reduce the number of uninhabitable houses. In the provision of assistance, of course, must be selected in advance in accordance with the conditions that have been determined. The large number of community data that is not appropriate but has already registered makes it difficult for the selection team to determine the people who are entitled to receive home renovation assistance, so that the provision of home renovation assistance provided is not right on target decision support. A decision support system is a system capable of solving a problem. One method that can be used for decision making is by using the Preference Ranking Organization Method for Enrichment Evaluations II. This method is used to make settlements based on existing criteria such as the eligibility status of the house, occupation, income, number of dependents, and age. Where each criterion has its own weight value and will be ranked to obtain the Net Flow value. This method will make it easier for the selection team to determine the most eligible recipients to receive home renovation assistance every year. After ranking, the results of the Preference Ranking Organization Method for Enrichment Evaluations II method are Rosdita Banjarnahor (P4) with the highest Net Flow value of 0,2791. These results can make it easier for the selection team to determine the more appropriate recipients of home renovation assistance.